Research on local seed potato value chain gaps and bottlenecks in Tajikistan. Potato production support and research to improve food security in Khatlon, Tajikistan - International Potato Center (International Potato Center, 2016)
This study examines potato value chains and recommends the promotion of potato as a tool for improving diets and decreasing child malnutrition. It is necessary to ensure that farmers have access to quality seed, fertilizers and pesticides, as well as light machinery, to improve seed potato production.